A introdução da circularidade nas compras públicas através da nova lei de licitações: o papel da governança e do planejamento nos processos licitatórios - Amorim, Rodrigo Mascarenhas (2024)
Depletion of natural resources, climate change, pollution, and the need to reduce social inequality and poverty are factors that have hindered the control and management of available resources, imposing new ways of thinking, doing, and using. This has led to the circular economy (CE) gaining strength as an alternative model that seeks to mitigate resource depletion, waste, and emissions of gases. The CE requires rapid changes in consumption, production, policies, attitudes, and practices aimed at maximizing the efficiency of the life cycle of resources, goods, and services. Given its significant position in the economy and the high values involved, public procurement plays a fundamental role in driving the sustainability agenda. Even with delays in regulatory terms and, especially, in practical terms, Brazilian legislation has advanced in this direction with the introduction of life cycle assessment of the object when analyzing the proposal capable of generating the most advantageous result. This study aimed to verify how governance and planning of public procurement are being addressed at the Federal University of Sergipe (UFS) after the introduction of the life cycle perspective of the object through the new procurement law (Law No. 14,133/2021). This is a qualitative, exploratory study with a single-case strategy, adopting a pragmatic research perspective, which allows the use of various methods and worldviews and the adoption of different data collection and analysis techniques. UFS understands that issues related to sustainable procurement are a global trend and that the public service needs to set an example and start the process. UFS has satisfactory material and technological resources to achieve the objectives established in the New Procurement Law (NPL), but faces difficulties related to human resources. Strategic planning at UFS is still in its early stages, but senior management has been guiding sectors to align procurement with planning instruments. Short-term implementation, lack of analysis of the peculiarities of each agency, organizational culture, quantity, and qualification of human resources are the difficulties related to the implementation of governance in UFS procurement. The Planning Pro-Rector's Manager understands that there is alignment between planning instruments and studies, but that sustainability-related justifications are generic, without pertinent evaluation, and the search for sustainable solutions, as well as consideration of principles and practices in the CE, is incipient and/or nonexistent. Organizational culture, quantity and qualification of human resources, absence of process flow, where verification of the solution presented by the requesting units is necessary, are the main difficulties related to aligning procurement with planning instruments. This work may assist public administration in the aspect related to sustainable public procurement, but as it is an emerging discussion, it is necessary to deepen the debate on the role of governance and planning in public procurement.